(untitled) (ModaPalavra e-periódico, 2019)
This article purpose is to establish relations between the image construction of Tônia Carrero (1922-1955) as Brazilian cinema consecrated star trough photographs published by the magazines O Cruzeiro e Scena Muda during the period of 1947 and 1955 –when the Brazilian cinematographic production was industrialized and consequently the attempt of emplacing a star system similar to the Hollywoodian way. During this period, Tônia Carrero initiated her career and starred Vera Cruz Film Production Company (Companhia Cinematográfica Vera Cruz) movies, where she interpreted roles associated with the Hollywoodian good-bad girl archetype. In her photographs published by the press, her image construction as a star was reinforced using clothes, accessories, and postures that connected her image to the glamour or the naïve eroticism of pin-up women –an element which was also used by Hollywoodian cinema in its star construction.